Agency Conflict Management in Investment Stages of Startups with Venture Capital Funding - Ratih Mustikoningsih; Budi Frensidy (E-Jurnal Akuntansi, 2025)
This research aims to manage agency conflicts such as information asymmetry and moral hazard that occur during the pre-investment to post-investment phases. During the investment process, Venture Capital acts as the principal, while Startups act as the agents. This study employs a qualitative method with a case study approach. The research subjects consist of one (1) Startup in the financial technology (fintech) sector and two (2) Venture Capital firms, one owned by a State-Owned Enterprise (SOE) and the other privately owned. The findings indicate that managing agency conflicts between Venture Capital and Startups requires comprehensive pre-investment assessments, including initial selection that covers financial and non financial aspects, as well as contractual agreements involving a due diligence process. Meanwhile, post-investment management is carried out through performance monitoring, staged funding, and forming a Venture Capital Syndicate.